EFFECT OF GAP DISTURBANCES ON SOIL PROPERTIES AND UNDERSTORY PLANT DIVERSITY IN A PINUS MASSONIANA PLANTATION IN HUBEI, CENTRAL CHINA - Wen-Jie Hu; Peng-ChengWang; Yu Zhang; Ming-JunTeng; Zhi-XiangZhou (Journal of Animal and Plant Sciences, 2016)
The response of plant species composition, diversity and soil nutrient availability to different canopysizes and age gaps in a Pinus Massoniana plantation were surveyed in Taizishan, Hubei province, central China. The soil chemical properties of 27 gaps and 3 non-gaps were measured and compared. The study objectives were: (a) confirm whether and when nutrient pulses emerged in small gaps; (b) determine the effects of gap sizes and ages on the soil properties and species diversity in gaps; and (c) determine the response of species diversity to soil nutrient variables in gaps. The understory plants of all canopy gaps and non-gaps were identified. Diversity indices were employed in this study, and the relationship between understory plant diversity and soil chemical properties were analyzed by detrended canonical correspondence analysis (DCCA). The results showed that soil properties and species diversity were significantly impacted by forest gaps, and the effects of the gap ages were more extensive than those of the gap sizes. The nutrient pulses occurred in gaps, but the emergence of nutrient indicators pulses in different age and size gaps was different.
Keywords: disturbance; gap size; gap age; soil properties; species diversity